IDENTIFIKASI MEMBACA PERMULAAN DI KELAS 1 SDN PANDEANLAMPER 05 SEMARANG - Muhamad Habib Syukron Hidayat; Diana Endah Handayani; Asep Ardiyanto (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
The uneven distribution of basic literacy skills and limitations in visual cognitive processing in early childhood in interpreting textual symbols are the background of this research activity. These operational problems trigger obstacles in information absorption, lethargy of instructional focus, and ongoing academic vulnerability for students in early grades. The main focus of this scientific study is to identify early reading skills and dissect the multidimensional factors that influence these obstacles. The steps of a descriptive qualitative approach with an interactive analysis design are carried out through direct observation techniques, semi-structured interviews, and documentation of draft learning records. Primary data collection is carried out periodically with subjects of first grade A students, class teachers, and the principal at SDN Pandeanlamper 05 Semarang. Data validity is tested through triangulation of techniques and sources. Empirical research findings reveal that of a total of 27 students, 15 children are in the high category, while 12 students are identified as having mechanical obstacles divided into 5 students in the low category and 7 students in the moderate category. The subjects' operational difficulties are dominated by errors in distinguishing similar letter shapes experienced by 9 children. Inhibiting factors include physiological, intellectual, cyber environmental, and psychosocial variables. The main conclusion emphasizes the importance of synergistic collaboration in designing a diverse literacy conditioning strategy. ABSTRAK Ketidakmerataan kecakapan literasi dasar serta keterbatasan pemrosesan kognitif visual pada anak usia dini dalam mencerna simbol tekstual melatarbelakangi kegiatan penelitian ini. Masalah operasional tersebut memicu terhambatnya penyerapan informasi, kelesuan fokus instruksional, serta kerentanan akademis berkelanjutan bagi para siswa di jenjang kelas awal. Fokus utama kajian ilmiah ini adalah mengidentifikasi kemampuan membaca permulaan serta membedah faktor-faktor multidimensional yang memengaruhi hambatan tersebut. Langkah-langkah pendekatan kualitatif deskriptif dengan desain analisis interaktif ini dijalankan melalui teknik observasi langsung, wawancara semi-terstruktur, dan dokumentasi draf rekam belajar. Pengumpulan data primer dilaksanakan berkala terhadap subjek siswa kelas satu A, guru kelas, dan kepala sekolah di SDN Pandeanlamper 05 Semarang. Validitas data diuji via triangulasi teknik dan sumber. Temuan penelitian secara empiris menyingkap bahwa dari total 27 siswa, sebanyak 15 anak menempati kategori tinggi, sedangkan 12 siswa teridentifikasi mengalami hambatan mekanis yang terbagi atas 5 siswa berkategori rendah dan 7 siswa berkategori sedang. Kesulitan operasional subjek didominasi oleh kekeliruan membedakan bentuk huruf mirip yang dialami oleh 9 anak. Faktor penghambat mencakup aspek fisiologis, intelektual, lingkungan siber, dan variabel psikososial. Simpulan utama menegaskan pentingnya kolaborasi sinergis guna merancang draf strategi pengondisian literasi bervariasi.